To Siberia [large type] - Petterson, Per) 1952- (Kennebec Large Print, 2009)
In the years before the Nazis arrive, two young people growing up in Danish Jutland have dreams of leaving their frigid coastal town while coping with distant parents, eccentric family members, and the cold winds. In the aftermath of their grandfather's suicide, the arrival of puberty and most tragically, the German invasion, their idyllic childhood changes forever.